PEMANFAATAN SUMBER BELAJAR DALAM PENGEMBANGAN KARAKTER PESERTA DIDIK - Mega Dwi Susanti (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2018)
Primary education can build the students’ character through many kinds of learning sources. Learning sources is anything which can be used to optimalize the result of the study. It can be seen not only from the result but also the process of students’ interaction with many kinds of learning sources which can motivate them to study and increase their understanding in a certain lesson. The use of learning sources can be used as one of ways in developing the students’ character. There are several ways in using learning sources in MI Nurul Islam Mirigambar and MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung. The focus of this thesis are (1) How to choose the use of learning sources in developing the students’ character in MI Nurul Islam Mirigambar and MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung (2) How is the process in using learning sources in MI Nurul Islam Mirigambar and MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung (3) How is the result of using learning sources in MI Nurul Islam Mirigambar and MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung. The purpose of this study are to explain and describe (1) To know the way in choosing the use of learning sources in developing students’ character in MI Nurul Islam Mirigambar and MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagungs (2) To know the process in using learning sources in developing the students’ character in MI Nurul Islam Mirigambar and MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung (3) To know the result of using learning sources in developing the students’ character in MI Nurul Islam Mirigambar and MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung. The method of this study is using qualitative study that is multisite. The locations are in MI Nurul Islam Mirigambar and MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung. The data sources of this study are informant, event, location and document. The kinds of data are primary and secondary data. The technique of this study are individual site data and analysis and multisite data analysis while the data validation uses, credibility, dependability, transferability and information. From this study, the writer can conclude: (1) the way in choosing learning sources to develop the students’ character in MI Nurul Islam Mirigambar and MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung is very comprehensive. It covers adaptation of students’ character application and the environment (2) the process of using learning sources in developing students’ character in MI Nurul Islam Mirigambar has integrated in school regulation and then it’s socialized and implemented the schedule orderly along with organizer team and in MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung implement it through application which can be separated into several kinds, they are daily routine and organizing (3) the result of using learning sources in developing students’ character in MI Nurul Islam Mirigambar can be devided into religious character, discipline, caring to environment, responsible, creative, loving reading and standing alone, white in MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung covers religious character, discipline, responsible, friendly, communicative, standing alone and honest.